Efficiency of pay for performance program on the brazilian judiciary - Jesus-Silva, Luis Cláudio de; Marques, Antônio Luiz; Zogahib, André Luiz Nunes (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This article aims to examine the variable compensation program for performance implanted in the Brazilian Judiciary. For this purpose, a survey was conducted with the servers of the Court of Justice of the State of Roraima - Amazon - Brazil. The strategy consisted of field research with quantitative approach, with descriptive and explanatory research and conducting survey using a structured questionnaire, available through the INTERNET. The population surveyed, 37.79% is the sample. The results indicate the effectiveness of the program as a tool of motivation and performance improvement and also the need for some adjustments and improvements, especially on the perception of equity of the program and the distribution of rewards.